Electro-chemical oxidation and reduction of Ag as preparation for a high-efficiency surface enhanced Raman scattering (SERS) substrate - Lee, Jaeyeong; Hyun, Saebyul; Choi, Kyoung Soon; Jeon, Cheolho; Yu, Hak Ki (Journal of the Electrochemical Society, 2019)
Use of a silver (Ag) nanostructure as a high-efficiency SERS substrate has been proposed. The Ag film was first oxidized using the electro-chemical method for enlarging surface area and was then reduced with heat-treatment under a hydrogen (H2) atmosphere. The H2 gas easily reduced the oxidized Ag and it was found that 100°C was the temperature at which the Ag reduced into a nanosized particles. Temperatures higher than 100°C cause Ag to agglomerate, this creates less surface area and removes the ‘hot spot’ which is important to increase SERS efficiency. Rhodamine 6G was used as an analyte for the SERS measurement. Compared to the normal as-deposited Ag substrate (which has flat surface), an increase of approximately 250-fold higher SERS signal was obtained from Ag reduced at 100°C, and an increase of approximately 50-fold higher SERS signals from Ag reduced at 200°C and 300°C.
Keywords: Electrochemical method; Flat surfaces; High-efficiency; Nano-sized particles; Rhodamine 6G; SERS substrate; Surface area; Surface enhanced Raman Scattering (SERS)